Organizational alignment using the balance scorecard approach: case study of a malaysian government-linked company / Hazeline Ayoup - Ayoup, Hazeline (2015)
The Balanced Scorecard (BSC) constitutes one of the most popular performance measurement systems for organizations. Used solely as a performance measurement system, the BSC highlighted a serious setback: inability of the traditional management systems to link a company’s long-term vision with its short-term strategies. Premised on this deficiency, the BSC application has been further innovated to include using it as an organizational alignment tool. Specifically, the strategic use of BSC as an organizational alignment tool has been proposed by Kaplan and Norton in their 2006’s book Alignment: Using BSC to Create Corporate Synergies. Despite the detail implementation framework outlined in their book, there has been very limited literature written by previous researchers or practitioners to implicate the usage of BSC as an alignment tool. Most works on BSC were based mainly on its role as a performance measurement tool or premised on limited, superficial and generic data. The present study examines the use of BSC as an organizational alignment tool in a large government-linked company (GLC) in Malaysia. To be named as ATB, the case study company was one of the pioneer companies to implement BSC in this country way back in 1996. The use of BSC as an alignment tool became prominent for ATB when the “GLC Transformation Programme” was introduced by the government and came into effect in 2006. This study demonstrates how ATB uses the BSC to create organizational alignment and addresses organizational issues faced by the company in the process. Data for this study were gathered through interviews, analysis of documents, observations and a survey to the company’s employees. The study found that the BSC helps the case company to create organizational alignment only to a certain extent. Failure to enjoy full benefit of the BSC as an organizational alignment tool is due to the lack of understanding in executing the framework. This study discovers that the level of alignment created using this framework is subject to the comprehensiveness of its adoption by the employees from various levels. This study also found that organizational alignment requires organization to align its technical behavioral elements simultaneously. The study highlighted that the key determinant to organizational alignment using the BSC is the effectiveness of the KPIs determination process. The KPIs helps to connect and align these elements. Result of this study suggested that managers’ skill and knowledge, effective communication, partnership, restructuring, leadership, managers’ acceptance, trust, managers’ intention and attitudes, managers’ involvement and commitment affect the process of determining appropriate KPIs in the case company. The study also outlined several contributions to the body of knowledge and practices. It extended the organizational alignment model developed by Kaplan and Norton (2006) to include the behavioral elements into the model. It also offers implementation guides to the practitioners and suggests several improvement initiatives. However, the finding of this study have to be carefully interpreted as it is only limited to the case company. Future study could focus on multiple case studies in different industries and relational study on the multiple factors affecting the process.